PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN LAMPUNG TENGAH - Kusairin Zen; Afdal Mazni; Suharto Suharto (Universitas Muhammadiyah Metro, 2021)
BPKAD Central Lampung Regency as a public organization must be able to have employees who are competent in carrying out their work in accordance with the applicable SOP. In addition, employee performance will increase if it is supported by a conducive and disciplined work environment that is formed in employee character. Discipline is not only related to attendance, but work results that are in accordance with the targeted time and quality resulting from the work. The formulation of the problem in this study are 1) Is there any influence of discipline on employee performance at the Regional Financial and Asset Management Agency of Central Lampung Regency? 2) Is there any influence of the work environment on employee performance at the Regional Financial and Asset Management Agency of Central Lampung Regency? 3) Is there any influence of discipline and work environment simultaneously on employee performance at the Regional Financial and Asset Management Agency of Central Lampung Regency? This research was conducted at the Regional Financial and Asset Management Agency of Central Lampung Regency. The sampling technique used proportional random sampling to 65 respondents, namely employees of the Regional Financial and Asset Management Agency of Central Lampung Regency. The analysis technique in this research is using multiple linear regression test. From the research results, it can be concluded that discipline and work environment have an influence on employee performance partially or simultaneously. This shows that disciplined employees will affect the way they work and result in increased performance. In addition, a conducive work environment supports employees to improve their performance so that these employees produce optimal performance in carrying out tasks and jobs on time